2014
DOI: 10.5194/amtd-7-3253-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison between CARIBIC aerosol samples analysed by accelerator-based methods and optical particle counter measurements

Abstract: Inter-comparison of results from two kinds of aerosol systems in the CARIBIC (Civil Aircraft for the Regular Investigation of the atmosphere Based on a Instrument Container) passenger aircraft based observatory, operating during intercontinental flights at 9-12 km altitude, is presented. Aerosol from the lowermost stratosphere (LMS), the extra-tropical upper troposphere (UT) and the tropical mid troposphere (MT) were investigated. Aerosol particle volume concentration measured with an optical particle counter … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…(Jäger and Deshler, 2003). Measurements in the LMS show that volcanic eruptions of Grimsvötn and Nabro in 2011 only had minor influence on the particle size distribution (Martinsson et al, 2014), and they were similar to size distributions obtained in periods of small volcanic impact . Therefore, the background size distribution reported by the latter authors was used in this work.…”
Section: Computing the Stratospheric Aodmentioning
confidence: 58%
See 1 more Smart Citation
“…(Jäger and Deshler, 2003). Measurements in the LMS show that volcanic eruptions of Grimsvötn and Nabro in 2011 only had minor influence on the particle size distribution (Martinsson et al, 2014), and they were similar to size distributions obtained in periods of small volcanic impact . Therefore, the background size distribution reported by the latter authors was used in this work.…”
Section: Computing the Stratospheric Aodmentioning
confidence: 58%
“…In addition, organics (Friberg et al, 2014;Murphy et al, 2014), meteoritic matter, soil dust, and volcanic ash can be found in stratospheric aerosol particles. The ash component decreases readily after a volcanic eruption as the large ash particles get gravitationally separated from the sulfate forming volcanic SO 2 layers and subside out of the stratosphere.…”
mentioning
confidence: 99%
“…The analyses are undertaken in high vacuum at room temperature which, compared to the atmospheric concentrations, leads to losses of volatile organic aerosol constituents. 59,60 Recent measurements find considerable quantities of ammonium nitrate in the Asian summer monsoon anticyclone. 61,62 If present in our samples, that compound most likely will be lost to the gas phase in the IAGOS-CARIBIC sampling line because of the elevated temperature (30°C) compared with atmospheric conditions at 10 km altitude and the resulting dry conditions (<0.1% relative humidity).…”
Section: Methodsmentioning
confidence: 99%
“…The uncertainty in the elemental analyses are estimated to be 10%, and the combined sampling and analytical uncertainties are 12%. 60 In this study two layers in the LMS are investigated: the lowest layer range from the dynamical tropopause, defined here at 1.5 PVU, to 5 PVU, and the upper layer spans 5-12 PVU. Potential vorticity (PV) values are obtained from ECMWF analyses on model levels by bilinear interpolation in the time and space to the location of the IAGOS-CARIBIC aircraft.…”
Section: Methodsmentioning
confidence: 99%
“…4). These three elements exclusively occur within the carbonaceous matrix, and are not abrasion products from ice particles hitting the aerosol inlet as the metallic particles described by Murphy et al (2004) and Martinsson et al (2014). Furthermore, none of the samples was collected Figure 2.…”
Section: Sem Analysis Of the Chemical Composition Of The Refractory Cmentioning
confidence: 99%